50 Years on - BC Perioperative Nursing Organization Attains a Milestone: If We Want to Know Where We Are Going We Need to Know Where We Came From - Knoll, Susan (Operating Room Nurses Association of Canada Journal, 2017)
Just last year the BC Operating Room Nurses Group (BCORNG), now the Perioperative Registered Nurses Association of BC (PRNABC), celebrated 50 years of promoting perioperative nursing education and practice since its inception in 1966. Almost since the beginning, BCORNG/PRNABC has advocated for a close relationship with the National Perioperative Nursing Organization, and has actively participated in the formation and growth of the Operating Room Nurses Association of Canada (ORNAC). This article includes some highlights from the last five decades of BCORNG/PRNABC with a focus on connections and experiences with ORNAC.